2013
DOI: 10.1080/02580136.2013.867397
|View full text |Cite
|
Sign up to set email alerts
|

Neurophenomenology: an integrated approach to exploring awe and wonder1

Abstract: Astronauts often report experiences of awe and wonder while traveling in space. This paper addresses the question of whether awe and wonder can be scientifically investigated in a simulated space travel scenario using a neurophenomenological method. To answer this question, we created a mixed-reality simulation similar to the environment of the International Space Station. Portals opened to display simulations of Earth or Deep Space. However, the challenge still remained of how to best capture the resulting ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 54 publications
1
29
0
2
Order By: Relevance
“…A first attempt to use virtual simulation to elicit awe was made by Reinerman-Jones et al (2013). These authors analyzed participants’ experiences of viewing the earth from a deep space perspective – the so called the “Overview Effect” (White, 1987; Yaden et al, 2016) – using a qualitative analysis.…”
Section: Using Virtual Reality To Study Awementioning
confidence: 99%
See 1 more Smart Citation
“…A first attempt to use virtual simulation to elicit awe was made by Reinerman-Jones et al (2013). These authors analyzed participants’ experiences of viewing the earth from a deep space perspective – the so called the “Overview Effect” (White, 1987; Yaden et al, 2016) – using a qualitative analysis.…”
Section: Using Virtual Reality To Study Awementioning
confidence: 99%
“…Reinerman-Jones et al (2013) used a mixed reality simulation as a new tool to investigate the phenomenological emergent features of awe experience. Indeed, they were also able to grasp an element of surprise, closer to the need for accommodation component of awe as well as a negatively valenced awe experience by creating a highly ecological experience of awe (Gallagher, 2013).…”
Section: Possible Issues Concerning the Use Of Virtual Reality In Awementioning
confidence: 99%
“…For instance, it has been found that participants who recalled an experience of awe reported feeling smaller relative to the environment, as measured through self-report questionnaires [7]. People who watched the Earth from space by using a virtual reality (VR) simulation reported feelings of awe and feeling small and insignificant in the face of the vast and incomprehensible universe [19,20]. In addition, in a recent study experimentally induced feelings of awe resulted in higher ratings on the "small-self-scale," consisting of items like 'I feel small or insignificant' and 'I feel the presence of something greater than myself' [8].…”
Section: Original Research Reportmentioning
confidence: 99%
“…Awe and perceived vastness may also cause a reduced focus on and awareness of one's self (Piff et al, 2015;van Elk et al, 2016;Zhang, Piff, et al, 2014). Several studies have reported that perceptually vast and awe-eliciting stimuli can induce the feeling of a "small self", characterized by a reduced focus on the self and its related concerns (Bockelman, Reinerman-Jones, & Gallagher, 2013;Campos, Shiota, Keltner, Gonzaga, & Goetz, 2013;Piff et al, 2015;Reinerman-Jones et al, 2013;van Elk et al, 2016). The notion that awe induces changes in the perception of the self is also supported by studies on the effects of natural environments (for review, see : Bratman, Hamilton, & Daily, 2012).…”
mentioning
confidence: 99%